Stand Out Online Portofolio Design with Flowbite for Beginers - Dzakiyuddin Rohman, Hilmi; Qaedi Setiawan, Muhammad Thirafi; Ginawan, Najla Maharani Dewi Tiawa; Nurbaya Ambo, Sitti; Jumail, Jumail; Adharani, Yana (Society : Jurnal Pengabdian Masyarakat, 2025)
This community engagement project aimed to enhance digital literacy by providing practical training on building online portfolios using Flowbite and Tailwind CSS. The initiative targeted students and beginners who lacked prior experience in creating web-based portfolios. Through a combination of webinars and hands-on workshops, participants were introduced to the fundamentals of portfolio design, User-Centered Design (UCD) principles, and modern UI development using Flowbite components. The project implemented a project-based learning approach to ensure both theoretical understanding and technical skills acquisition. The event was held virtually on July 14, 2025, and attended by 33 participants, with 21 actively engaged during the session. A pre-test and post-test were administered to evaluate learning outcomes. The results showed a significant improvement in participants' understanding, with the average score increasing from 73.5 to 87. Additionally, 95% of participants expressed satisfaction with the training format and content. The program successfully equipped participants with the necessary knowledge and skills to develop responsive and aesthetically pleasing online portfolios, contributing to their personal branding efforts in the digital era.